Dialectics of Association and Dissociation: Spaces of Valuation, Trade, and Retail in the Gemstone and Jewelry Sector. (1st January 2022) - Thomsen, Lotte; Hess, Martin
Abstract: This article aims to substantiate how processes of valuation translate between different registers of value. We develop an analytical framework of how valuation is intertwined with geographic origination and the geographies of association and dissociation, which establish how commodities and consumer products are either associated with, or dissociated from, matters that are beneficial or damaging for sales and brand reputation. The article focuses on the rather unexplored gemstone and jewelry sector, and shows how the analysis of value is not reducible to Marxist notions of exchange and use value but needs to take into account symbolic and sign value, and embrace dis/association dialectics. It develops a novel conceptual framework that draws upon the early work of Baudrillard on symbolic value, together with Marxian value theory, and mobilizes it for the analysis of association–dissociation dialectics and practices in global value chains. We are particularly concerned with the role of origination and provenance to highlight the intrinsically geographic dimensions of gemstones that are enacted by traders and retailers in the valuation process. The article shows how valuation and consumption of gemstone and jewelry play out through complex and multiscalar, relational associative and dissociative practices, which intertwine with revealed sustainability problems in the diamond industry. It also shows how a current rise in the value and popularity of colored stones interrelate with a corporate refocusing away from mined diamonds, and entails even more in-transparent supply networks.